Rural life of Bangladesh reflected in Hashem Khan's painting / Mohammad Ferdous Khan Shawon - Shawon, Mohammad Ferdous Khan (Universiti Teknologi MARA, Perak, 2021)
Hashem Khan is considered as one of the key figures in Bangladesh art scenario. Born in Chandpur, Hashem Khan was graduated from the Faculty of Fine Art, Dhaka University in 1961. He was a Professor at the Faculty of Fine Art, University of Dhaka with 44-year experience and retired in the year 2007. He has achieved Ekushey Padak and Independence Day Award (The highest civilian award in Bangladesh) for his significant contributions in art and culture. Rural lifestyle is very unique in Bangladesh. Many poets, musicians, visual artists have taken inspiration from rural culture and life style of Bangladesh. His works reproduce the natural beauty of the village, rural life, and plenty of other things. He has used traditional folk colours like yellow, orange and green in his paintings and used folk motifs. Hashem Khan has done semi-realistic style of narration to communicate to the common people and also used vibrant colours in his paintings. The researcher here has selected the works of the artist for discussion and analysis from the exhibitions which were held from 1980 to 2018 in different art galleries in Dhaka, the capital of Bangladesh and also from two catalogues, which articulate 143 plates. The researcher has analysed his contents of the paintings. Besides the researcher also closely analysed the colours, composition and forms of the painting.